Pendidikan Media Sosial bagi Anak dengan Pendekatan Partisipatif dan Problem Solving untuk Siswa Sekolah Dasar - Nafisatul Muna, Arina; Pasya, Abiyyu Mufid Jadid; Syaputri, Erin Enrika Ayu (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2024)
Social media has now become an integral part of daily life, influencing all layers of society, including children from Generation Alpha, born after 2013. This study aims to explore the impact of media sosial on children's development and the important role of parents in managing technology usage among children. The methodology implemented involves interactive seminars at SDN Cibeunying using a participatory approach, problem solving, and mentoring, along with an evaluation of effectiveness through pretest and posttest assessments. The seminar results show a significant increase in students' understanding of the dangers of media sosial and the need for parental supervision. Negative impacts such as communication disruption, exposure to age-inappropriate information, and health issues can be minimized with proper supervision. This paper emphasizes the importance of parental involvement and the educational environment in guiding children to use media sosial wisely and safely.